Prominent Zakat Institutions and Their Role in Advancing the Welfare of the Muslim Community in The Eastern Province of Sri Lanka - Raseethu Mohamed Kasjin; Mohamed Haniffa Mohamed , Nairoos (AL-FALAH : Journal of Islamic Economics, 2025)
Purpose: This study focuses on institutionalized, prominent Zakat organizations and their role in advancing the welfare of Muslim communities in Sri Lanka. The Muslim second minority community carried out the Zakat several decades ago with the introduction of Islam. The primary objectives of this study are to introduce prominent Zakat institutions and to analyze the welfare contribution over the past five years from 2019 to 2023. Design/Method/Approach: This study used a mixed method. The primary data were collected through interviews with official representatives from four Zakat institutions operating in the following regions: Akkaraipattu, Kattankudi, Kinniya, and Sammanthurai. The interviews lasted between 50 and 60 minutes each. Secondary data was sourced from annual official publications and reports of the Zakat institutions, focusing on statistical figures that provide a quantitative perspective to complement the qualitative insights from the interviews. The qualitative data were transcribed and analyzed using thematic analysis. The quantitative secondary data were analyzed using descriptive statistics and interpreted to provide more accurate insights. Findings: The study highlights varying growth rates in Zakat collection and fluctuations across regions, with some Zakat fund collections experiencing sharp increases. In contrast, others showed declining patterns during the COVID-19 pandemic. All institutions played a pivotal role in advancing the welfare of the Muslim community. They focused on housing, food security, and self-employment, with additional contributions to education, healthcare, and social welfare. Originality/Values: The study suggests that Zakat institutions re-evaluate the mechanism used for the collection process, keep good relations with payers, and create a provincial and national regulatory body that regulates the rules, monitors the services, prioritizes the sectors to be highly focused on distributions, and connects with the government.